The Politics of Modernization and the Misleading Approaches to Development. (1st July 2016) - ,
Abstract : This article deconstructs the theory of modernization and argues that the theory is a political propaganda to mislead the people of Third World countries; the social transformation the theory advocates is not for the development of Third World countries. Instead, modernization is actually gradually destroying the local productive capacity, while cultivating the Western individualism in the South. In Uganda, the policies to bring about modernization under economic reform have made the economy to be dominated by a service sector that neither creates ample employment opportunities nor earns foreign exchange for the country. They have undermined manufacturing and agriculture, and as a result, a large percentage of the population is experiencing food insecurity. The article concludes by arguing that Uganda should have learnt from China's self-determined reforms and China should also learn from Uganda's experience while contemplating to adopt further reforms under foreign pressure.